Pengembangan Produk Kuliner Ikan Kakatua Sebagai Pendukung Daya Tarik Wisata di Kepulauan Karimunjawa¬ - Amelia, Viona; Prasetyo, Danang (Indonesian Journal Publisher, 2025)
Indonesia boasts a diverse culinary heritage that serves as a significant asset within the creative economy sector, particularly in tourism. In recent years, Indonesia's culinary industry has experienced substantial growth, making a notable contribution to the Gross Domestic Product (GDP) of the creative economy. One untapped potential lies in regional culinary specialties, such as those in the Karimunjawa Islands, which are renowned for their natural beauty but lack a distinctive signature dish. This study aims to develop a unique culinary product made from parrotfish in Karimunjawa, with a focus on skill training, product testing, packaging, and marketing. The research utilizes the fishbone model to identify key issues and solutions. Findings reveal that parrotfish-based cuisine holds significant potential to be developed as a tourist attraction and a unique local souvenir, which, in turn, could improve the welfare of the local community. However, challenges related to infrastructure, limited access to clean water, and economic dependence on external regions remain significant barriers that need to be addressed. Additionally, efforts to conserve parrotfish must be considered to ensure the sustainability of Karimunjawa's natural resources.